Characterisation of GPS-TEC in the African equatorial and low latitude region and the regional evaluation of the IRI model. (June 2016) - Adebiyi, S.J.; Adimula, I.A.; Oladipo, O.A.
Abstract: With the increasing application of Global Navigation Satellite System (GNSS) products and services, knowledge of the Total Electron Content (TEC) variation is vital, particularly in historically under-sampled regions. The ionospheric induced-error, which is the largest and most variable error source of GNSS applications, is proportional to TEC along the satellite-receiver path. Simultaneous Global Positioning System (GPS) measurements from six African equatorial and low latitude stations in the southern hemisphere are used to investigate the latitudinal variation of TEC over the region during the year 2013, a year of moderate solar activity. The analysis reveals some detailed features of seasonal, month-to-month and solar activity dependence of TEC. The seasonal variation of TEC revealed that the daytime and the pre-midnight values of TEC for stations located close to the geographic equator is considerably higher in equinoxes and June solstice compared to stations farther from the equator, however, the difference is insignificant during the December solstice. The month-to-month variation of TEC shows semi-annual symmetry/asymmetry in TEC values for stations closer/farther from the equator. TEC sensitivity to solar activity shows significant seasonal and latitudinal characteristics. Generally, a relatively good correlation exists between TEC and F10.7 for stations around the Equatorial Ionization Anomaly (EIA) region compared to those found at stations close to the equator. Beyond the EIA region, the correlation coefficients drop in all seasons. TEC predicted by the three topside options of the International Reference Ionosphere (IRI) 2012 model [i.e. the NeQuick (NeQ), IRI-2001 Corrected (IRI-01 Corr) and the IRI-2001 (IRI-01) options] exhibits latitudinal and seasonal characteristics. The NeQ option performed better than the other two options at stations located within the equatorial region in most of the months and seasons. Outside the EIA region, the IRI-01 Corr and IRI-01 options give better predictions. Generally, the three model options give improved TEC representations with increasing latitude. Highlights: TEC values are higher over stations closer to the geographic equator in all the seasons. TEC values are lower over stations far from to the geographic equator in all the seasons. Monthly variation shows semi-annual symmetry and asymmetry in TEC values. IRI 2012-TEC using the topside options exhibits latitudinal and seasonal characteristics. TEC sensitivity to solar activity shows seasonal and latitudinal dependence.